Incidence of Keratoconus and Its Association with Systemic Comorbid Conditions: A Nationwide Cohort Study from South Korea - Jong Youn Moon; Jesang Lee; Yoon Hyung Park; Eun-Cheol Park; Si Hyung Lee (Journal of Ophthalmology)
Purpose. To determine the incidence of keratoconus and to determine its possible association with common systemic diseases using a nationwide cohort. Methods. This retrospective nationwide cohort study included 1,025,340 subjects from the Korean National Health Insurance Service-National Sample Cohort database from 2004 to 2013. Estimates for incidence rates of keratoconus were identified. After 1 : 5 matching using propensity scores, associations between keratoconus and certain systemic comorbidities were determined using multivariate logistic regression analysis. Results. The incidence during the same period was 15.1 cases per 100,000 person-years. Adjusted logistic regression analysis after propensity score matching revealed significant associations between keratoconus and allergic rhinitis (odds ratio (OR): 1.86; 95% confidence interval (CI): 1.63–2.13; p<0.001), asthma (OR: 1.20; 95% CI: 1.06–1.36; p<0.001), atopic dermatitis (OR: 1.33; 95% CI: 1.13–1.56; p<0.001), and diabetes mellitus (DM) (OR: 1.35; 95% CI: 1.15–1.58; p<0.001). Conclusion. Estimates of the incidence of keratoconus may help in the planning of eye-care policies, and the results of this study determined the associations between allergic diseases and keratoconus. Conflicting results regarding the association between keratoconus and DM should be further evaluated.